Advances in cryptology--EUROCRYPT 2016 : 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Vienna, Austria, May 8-12, 2016, proceedings /: 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Vienna, Austria, May 8-12, 2016, proceedings. ([2016]) - Unknown
No abstract available